The Anatomical Society core regional anatomy syllabus for undergraduate medicine. Issue 1 (27th November 2015) - Smith, C.F.; Finn, G.M.; Stewart, J.; Atkinson, M.A.; Davies, D.C.; Dyball, R.; Morris, J.; Ockleford, C.; Parkin, I.; Standring, S.; Whiten, S.; Wilton, J.; et al.
Abstract: The Anatomical Society's core syllabus for anatomy (2003 and later refined in 2007) set out a series of learning outcomes that an individual medical student should achieve on graduation. The core syllabus, with 182 learning outcomes grouped in body regions, referenced in the General Medical Council's Teaching Tomorrow's Doctors, was open to criticism on the grounds that the learning outcomes were generated by a relatively small group of anatomists, albeit some of whom were clinically qualified. We have therefore used a modified Delphi technique to seek a wider consensus. A Delphi panel was constructed involving 'experts' ( n = 39). The revised core syllabus of 156 learning outcomes presented here is applicable to all medical programmes and may be used by curriculum planners, teachers and students alike in addressing the perennial question: 'What do I need to know ?'